Frailty and Sarcopenia in Older Patients Receiving Kidney Transplantation - Gandolfini, Ilaria; Regolisti, Giuseppe; Bazzocchi, Alberto; Maggiore, Umberto; Palmisano, Alessandra; Piotti, Giovanni; Fiaccadori, Enrico; Sabatino, Alice (Frontiers in Nutrition, 2019)
Kidney transplantation is the treatment of choice for most of the patients with end-stage renal disease (ESRD). It improves quality of life, life expectancy, and has a lower financial burden to the healthcare system in comparison to dialysis. Every year more and more older patients are included in the kidney transplant waitlist. Within this patient population, transplanted subjects have better survival and quality of life as compared to those on dialysis. It is therefore crucial to select older patients who may benefit from renal transplantation, as well as those particularly at risk for post-transplant complications. Sarcopenia and frailty are frequently neglected in the evaluation of kidney transplant candidates. Both conditions are interrelated complex geriatric syndromes that are linked to disability, aging, comorbidities, increased mortality, and graft failure post-transplantation. Chronic kidney disease (CKD) and more importantly ESRD are characterized by multiple metabolic complications that contribute for the development of sarcopenia and frailty. In particular, anorexia, metabolic acidosis and chronic low-grade inflammation are the main contributors to the development of sarcopenia, a key component in frail transplant candidates and recipients. Both frailty and sarcopenia are considered to be reversible. Frail patients respond well to multiprofessional interventions that focus on the patients' positive frailty criteria, while physical rehabilitation and oral supplementation may improve sarcopenia. Prospective studies are still needed to evaluate the utility of formally measuring frailty and sarcopenia in the older candidates to renal transplantation as part of the transplant evaluation process.